2014
DOI: 10.3389/fcimb.2014.00042
|View full text |Cite
|
Sign up to set email alerts
|

Bioaerosols from composting facilities—a review

Abstract: Bioaerosols generated at composting plants are released during processes that involve the vigorous movement of material such as shredding, compost pile turning, or compost screening. Such bioaerosols are a cause of concern because of their potential impact on both occupational health and the public living in close proximity to such facilities. The biological hazards potentially associated with bioaerosol emissions from composting activities include fungi, bacteria, endotoxin, and 1-3 β-glucans. There is a majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 55 publications
3
33
0
2
Order By: Relevance
“…It was further identified as characteristic for epiphytic freshwater communities with hypothesised metabolic functions including hydrolytic capability (Ivanova et al, 2018), metabolism of complex compounds (van Kessel et al, 2011), anammox-pathways (Chu et al, 2015) and high ozone resistance (Tian et al, 2017), Planifilum (family Thermoactinomycetaceae), a thermophilic, spore-forming, filamentous, gram-positive, facultative anaerobe Bacilli genus was found in hot springs , compost (Han et al, 2013;Hatayama et al, 2005) and sludge compost (Yu et al, 2015). Planifilum is present in a range of bioaerosol studies from pharmaceutical indoor air and dominated other phylotypes in thermophilic composting bioaerosols (Le Goff et al, 2010;Wéry, 2014). It also occurred with high viable abundances in a controlled clean room for space craft assembly (Mahnert et al, 2015), which indicated its adaption to harsh environments.…”
Section: Indicator Genera and Classesmentioning
confidence: 99%
“…It was further identified as characteristic for epiphytic freshwater communities with hypothesised metabolic functions including hydrolytic capability (Ivanova et al, 2018), metabolism of complex compounds (van Kessel et al, 2011), anammox-pathways (Chu et al, 2015) and high ozone resistance (Tian et al, 2017), Planifilum (family Thermoactinomycetaceae), a thermophilic, spore-forming, filamentous, gram-positive, facultative anaerobe Bacilli genus was found in hot springs , compost (Han et al, 2013;Hatayama et al, 2005) and sludge compost (Yu et al, 2015). Planifilum is present in a range of bioaerosol studies from pharmaceutical indoor air and dominated other phylotypes in thermophilic composting bioaerosols (Le Goff et al, 2010;Wéry, 2014). It also occurred with high viable abundances in a controlled clean room for space craft assembly (Mahnert et al, 2015), which indicated its adaption to harsh environments.…”
Section: Indicator Genera and Classesmentioning
confidence: 99%
“…Aerobiology is the research area focusing on the generation and transport of bioaerosols. Bioaerosols are small, airborne particles consisting of biological material (from bacteria, viruses, spores, fungi, algae, protozoa, and pollen) either attached to particulate matter or not (Bovallius and Roffey, 1987;Després et al, 2012;Dungan, 2010;Gilbert and Duchaine, 2009;Griffin, 2007;Stärk, 1999;Wéry, 2014). Large amounts of bioaerosols are produced each year by sources in-…”
Section: Perspective On Bioaerosolsmentioning
confidence: 99%
“…Biowaste facilities are commonly studied to assess workers' exposure because of the intense microbial activity involved in waste degradation and because of the types of activities performed by workers (Bonifait et al 2017;Dubuis et al 2017;Mbareche et al 2017a;Van Kampen et al 2014;Wéry 2014;Wouters et al 2006). Farms are another example of workplace settings where bioaerosol exposure is complex.…”
Section: Exposure Studies and Health Risksmentioning
confidence: 99%